2021
DOI: 10.54910/sabrao2021.53.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the submergence stress tolerance of local South Sumatran rice through the introgression of the Sub1 gene by using marker-assisted selection

Abstract: Submergence stress due to unpredictable soil flooding is one of the main constraints encountered in rainfed growing areas, especially in Southern Sumatran riparian swamps. The development of submergence-stress-tolerant cultivars through the introgression of Sub1 via marker-assisted backcrossing (MABC) is an ideal solution. This study was carried out during 2020 at Sriwijaya University, Palembang, Indonesia, with the aim to select Sub1-introgressed lines in BC3F1 generations on the basis of MABC and to screen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Samples were amplificated in a single 96-well PCR (Biologix) with a total volume of 12.5 μL reactions containing of 0.5 μL template DNA from Inpara 8, Inpago 5, and BC2F1 generations; 0.5 μL the forward and reverse primers; 4.75 μL of MyTaq DNA polymerase (Bioline, BIO); and 6.25 μL of ddH2O. After pre-denaturation at 94°C for 5 min, the amplification was followed a procedure by Adriansyah et al [12] with 34 cycles; each cycle comprised 1 min of denaturation at 94°C, 1 min of annealing at 55°C, 2 min of extension at 72°C, and 2 min of final extension at 72°C. The PCR product was mixed with loading dye gel and separated by electrophoresis on 1% agarose gel in 1x TBA with 100 bp DNA ladder (Promega, USA) to determine the amplicon size.…”
Section: Molecular Marker Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Samples were amplificated in a single 96-well PCR (Biologix) with a total volume of 12.5 μL reactions containing of 0.5 μL template DNA from Inpara 8, Inpago 5, and BC2F1 generations; 0.5 μL the forward and reverse primers; 4.75 μL of MyTaq DNA polymerase (Bioline, BIO); and 6.25 μL of ddH2O. After pre-denaturation at 94°C for 5 min, the amplification was followed a procedure by Adriansyah et al [12] with 34 cycles; each cycle comprised 1 min of denaturation at 94°C, 1 min of annealing at 55°C, 2 min of extension at 72°C, and 2 min of final extension at 72°C. The PCR product was mixed with loading dye gel and separated by electrophoresis on 1% agarose gel in 1x TBA with 100 bp DNA ladder (Promega, USA) to determine the amplicon size.…”
Section: Molecular Marker Analysismentioning
confidence: 99%
“…A tightly-linked SSR marker, SUB1C173 [17] used for foreground selection (Table 1). The foreground marker used in this study also used by Septiningsih et al [18], Iftekharaddaula et al [13], Mojulat et al [19], and Adriansyah et al [12] to identify Sub1 gene introgressed. In foreground selection, the heterozygous plants were selected, then proceed to background selection.…”
Section: Selection Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Chozin et al (2017) suggested to improve rice yield tackled by the genetic and physiological natures. So, increasing of productivity in suboptimal area with adaptive characters and higher production in submergence condition can be initiated by introgressed Sub1 gene in rice cultivar which has good agronomy character (Adriansyah et al 2021). Tiwari et al, (2017) obtained a dual tolerant rice line in submergence and drought conditions, from crosses between Swarna Sub1 x NDR 9830102.…”
Section: Introductionmentioning
confidence: 99%